2019
DOI: 10.13057/biodiv/d200211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic diversity, heritability, and correlation between the quantitative characters on 30 sweet potato germplasms in Lampung, Indonesia

Abstract: Dewi R, Utomo SD, Kamal M, Timotiwu PB, Nurdjanah S. 2019. Genetic and phenotypic diversity, heritability, and correlation between the quantitative characters on 30 sweet potato germplasms in Lampung, Indonesia. Biodiversitas 20: 380-386. Local food commodities such as sweet potato is an alternative rice substitute food which has high nutritional content. Estimating the value of genetic diversity, heritability and correlation between quantitative characters with the weight of large storage root per plant, is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…While the medium heritability value on the character shows that the influence of the environment and genotype is at the same level. The similar result were obtain by Dewi et al, (2019) that reported the weight of vines, number of large root, and weight of root that showed high heritability values. Root yield, harvest index, and root dry matter content also show high heritability values on study by Shumbusha et al, (2019) High heritability coupled with broad GCV indicated that the characters had additive gene effect and more reliable for effective selection.…”
Section: Estimation Of Genetic Variance Componentsupporting
confidence: 84%
See 1 more Smart Citation
“…While the medium heritability value on the character shows that the influence of the environment and genotype is at the same level. The similar result were obtain by Dewi et al, (2019) that reported the weight of vines, number of large root, and weight of root that showed high heritability values. Root yield, harvest index, and root dry matter content also show high heritability values on study by Shumbusha et al, (2019) High heritability coupled with broad GCV indicated that the characters had additive gene effect and more reliable for effective selection.…”
Section: Estimation Of Genetic Variance Componentsupporting
confidence: 84%
“…The high heritability value shows that the character is more influenced by genetic factors. A character that has a high heritability value can be used as an effective selection criteria in the early generations (Chahal & Gosal 2010;Afuape et al, 2015;Dewi et al, 2019). -i 23.50 a-h 2.86 c-g 3.21 f-j 0.98 a-e 0.29 e-h 11.66 e-h 0.26 d-k 34.93 a 5 MLGI 0009 160.20 h-k 19.15 a 30.00 b-g 24.00 a-h 3.41 b-e 9.02 b-e 1.12 a-e 0.64 b-d 25.61 b-d 0.34 b-f 30.04 c 6 MLGI 0011 184.20 f-h 15.00 a-g 26.00 c-i 14.50 f-h 2.39 c-g 5.27 e-j 0.54 de 0.34 e-h 13.62 e-h 0.28 d-j 31.23 b 7 MLGI 0012 166.30 h-j 16.80 a-d 36.50 b-d 19.00 c-h 3.21 b-f 6.74 d-g 1.32 a-e 0.47 c-e 18.65 c-e 0.32 c-g 28.79 8 MLGI 0014 301.90 b 11.50 d-h 14.50 e-i 12.00 h 1.51 e-g 3.40 f-j 0.46 de 0.23 e-h 8.89 e-h 0.25 d-k 23.64 m 9 MLGI 0018 155.60 h-k 11.70 d-h 23.50 c-i 6.50 h 1.64 e-g 6.85 c-g 0.30 e 0.40 d-g 15.71 d-g 0.34 b-f 31.25 b 10 MLGI 0021 68.96 n 12.20 d-h 9.00 i 16.50 f-h 1.40 fg 1.78 j 0.62 de 0.13 gh 5.22 gh 0.16 h-l 28.15 g 11 MLGI 0023 115.30 lm 13.40 b-g 15.50 e-i 42.50 a-d 3.32 b-f 2.75 g-j 1.79 a-c 0.26 e-h 10.37 e-h 0.25 d-k 27.92 h 12 MLGI 0027 215.30 ef 16.60 a-e 14.50 e-i 15.00 f-h 2.04 d-g 1.87 ij 0.49 de 0.16 f-h 6.49 f-h 0.13 kl 33.77 13 MLGI 0030 149.20 i-k 13.00 b-g 13.50 f-i 19.00 c-h 2.01 d-g 1.84 j 0.47 de 0.14 f-h 5.71 f-h 0.15 i-l 27.76 h 14 MLGI 0031 127.80 k-m 16.50 a-f 10.50 hi 9.50 h 1.25 g 1.53 j 0.30 e 0.11 h 4.51 h 0.10 l 29.54 e 15 MLGI 0035 177.70 g-i 13.75 a-g 33.00 b-e 18.50 d-h 3.37 b-e 10.93 bc 0.90 a-e 0.76 ab 30.41 ab 0.44 a-c 24.53 k 16 MLGI 0037 264.50 c 13.70 a-g 38.50 bc 23.00 b-h 3.15 b-g 16.71 a 1.34 a-e 0.92 a 36.89 a 0.56 a 24.61 k 17 MLGI 0046 172.30 h-j 14.80 a-g 23.00 c-i 21.00 b-h 2.54 c-g 5.16 e-j 0.93 a-e 0.35 e-h 14.12 e-h 0.29 c-i 32.26 18 MLGI 0047 253.30 cd 15.20 a-g 11.00 g-i 17.50 e-h 2.09 d-g 1.88 ij 0.66 c-e 0.18 f-h 7.23 f-h 0.14 j-l 34.88 a 19 MLGI 0048 282.60 bc 13.50 b-g 19.00 d-i 14.00 gh 1.88 d-g 3.08 f-j 0.57 de 0.21 e-h 8.29 e-h 0.21 e-l 27.27 i 20 MLGI 0050 346.10 a 17.90 a-c 22.50 c-i 23.00 b-h 2.57 c-g 5.45 e-j 1.13 a-e 0.37 d-h 14.97 d-h 0.26 d-k 26.69 j 21 MLGI 0057 75.20 n 12.20 d-h 25.50 c-i 27.50 a-h 3.22 b-f 3.18 f-j 1.09 a-e 0.26 e-h 10.35 e-h 0.30 c-i 26.80 j 22 MLGI 0058 228.70 de 18.20 ab 30.50 b-f 45.00 ab 4.20 bc 2.44 h-j 1.39 a-e 0.21 e-h 8.51 e-h 0.18 g-l 29.85 cd 23 MLGI 0059 208.90 e-g 11.90 d-h 13.50 f-i 24.00 a-h 2.19 d-g 1.99 ij 0.82 b-e 0.16 f-h 6.55 f-h 0.19 f-l 29.36 ef 24 MLGI 0065 108.30 m 7.30 h 29.50 b-h 43.00 a-c 3.73 b-d 4.82 f-j 1.96 a 0.35 e-h 13.95 e-h 0.48 ab 26.06 25 MLGI 0066 162.70 h-j 16.70 a-d 30.00 b-g 21.00 b-h 2.87 c-g 3.17 f-j 0.90 a-e 0.23 e-h 9.10 e-h 0.20 e-l 29.75 d 26 MLGI 0070 213.88 ef 11.00 gh 33.50 b-e 22.00 b-h 3.14 b-g 11.29 b 1.35 a-e 0.73 a-c 29.06 a-c 0.53 a 27.13 i 27 MLGI 0076 224.60 de 11.10 f-h 19.00 d-i 8.00 h 1.76 e-g 4.55 f-j 0.30 e 0.31 e-h 12.43 e-h 0.31 c-h 24.16 l 28 MLGI 0077 141.60 j-l 7.50 h 15.00 e-i 21.00 b-h 2.17 d-g 1.80 j 0.70 c-e 0.16 f-h 6.31 f-h 0.25 d-l 28.23 g 29 MLGI 0079 219.20 e 14.10 a-g 35.50 b-d 43.00 a-c 4.30 bc 6.00 d-i 1.51 a-d 0.41 d-f 16.33 d-f 0.35 b-e 25.74 30 MLGI 0080 182.80 f-h 11.20 e-h 24.50 c-i 38.00 a-g 3.71 b-d 2.86 f-j 1.32 a-e 0.25 e-h 9.83 e-h 0.28 d-k In this study, heritability value showed that almost all of the characters observed have high broad-sense heritability except for the weight of the non-saleable root (Table 5).…”
Section: Estimation Of Genetic Variance Componentmentioning
confidence: 99%
“…They found that conventional propagation method gave the highest growth rates, however the difference in yield between the conventional propagation and tissue culture regenerated plants did not vary significantly. Moreover, Dewi et al [20] explained that the sweet potato characters like weight of large storage roots, number of large storage roots, storage root length, storage root diameter, vines length, segment length, vines diameter, and weight of vines had a value of genetic diversity. The germplasm of 30 sweet potato genotypes found in Lampung could be selected and crossed to create the desired superior characters.…”
Section: Sweet Potato Breedingmentioning
confidence: 99%
“…Genetic factors influenced the characters found in sweet potato genotypes. Phenotypic in 30 sweet potato genotypes found at the Politeknik Negeri Lampung has an extensive genetic and phenotypic diversity and high heritability (Dewi et al 2019).…”
Section: D E a Bmentioning
confidence: 99%
“…is one of the primary sources of carbohydrates that is quite preferred and has potential as a rice substitute. Sweet potato is an alternative rice substitute food that has high nutritional content (Dewi et al 2019). It is suitable for production on marginal lands and has an essential role as a food (Motsa et al 2015).…”
Section: Introductionmentioning
confidence: 99%